Blending thermal crosslinking diaphragm for all-vanadium redox flow battery, preparation method and application

By blending sulfonated benzooxazine with sulfonated polyether ether ketone in an all-vana liquid flow battery and thermally crosslinking, the problem of insufficient chemical stability and mechanical properties of SPEEK membranes is solved, and higher ion selectivity and battery performance are achieved.

CN119560601APending Publication Date: 2025-03-04NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411438031.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

SPEEK membrane has low chemical stability and poor mechanical properties in all vanadium flow batteries, which affects the application of the battery.

Method used

A covalent crosslinking film with a network structure was prepared by blending sulfonated benzooxazine with sulfonated polyether ether ketone and crosslinking by thermal curing.

Benefits of technology

This thermal crosslinked membrane significantly improves ion selectivity and mechanical properties in all vanadium flow cells, enhances Coulomb efficiency, and improves the dimensional stability of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560601A_ABST
    Figure CN119560601A_ABST
Patent Text Reader

Abstract

The invention discloses synthesis of a sulfonated benzoxazine material (SBA) suitable for an all-vanadium redox flow battery and thermal crosslinking application of the SBA and sulfonated polyether-ether-ketone (SPEEK). According to the sulfonated benzoxazine material, a hydrophilic group sulfonic acid group is connected to a benzene ring and an N and O six-membered oxazine ring, so that the proton conductivity is enhanced while the characteristics of low curing shrinkage rate, high modulus, high strength, good heat resistance, low water absorption rate and the like of the benzoxazine material are retained. The covalent cross-linked membrane with a net-shaped structure is prepared by mixing the covalent cross-linked membrane with SPEEK with high proton conductivity and then carrying out thermal crosslinking by adopting thermal curing, so that the covalent cross-linked membrane with the net-shaped structure is prepared. On one hand, hydrophilic sulfonic acid groups carried by sulfonated polyetheretherketone and sulfonated benzoxazine form a hydrophilic structural domain, so that the proton conductivity is enhanced; on the other hand, a net structure formed by thermal crosslinking has excellent ion selectivity, the vanadium resistance is enhanced, the mechanical property and the dimensional stability are improved, and the free volume of a sulfonated polyether ether ketone matrix is limited by a crosslinking structure, so that the water absorption rate of the membrane is also greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a thermally crosslinked film for vanadium redox flow batteries, its preparation method, and its applications, belonging to the field of vanadium redox flow battery technology. Background Technology

[0002] In recent years, with the introduction of the "dual carbon" concept, the demand for and utilization of renewable energy sources such as wind and solar power have received increasing attention. However, large-scale integration of these random and intermittent renewable energy sources will greatly disrupt the stability of the power grid system. Therefore, it is necessary to configure appropriate energy storage systems on both the generation and user sides to stabilize intermittency and fill the gap between generation and load.

[0003] Vanadium redox flow batteries (VRFBs), as a type of chemical energy storage, feature independently designed power and capacity. They offer advantages such as easy scalability, high safety, no cross-contamination, long lifespan, and environmental friendliness, making them well-suited for large-scale energy storage applications. Currently, SPEEK membranes are widely used in VRFBs due to their excellent proton conductivity; however, their low chemical stability and poor mechanical properties severely limit their application. Therefore, developing novel, low-cost, high-efficiency, and long-life membranes is of great significance to the development of VRFBs. Summary of the Invention

[0004] The technical problem this invention aims to solve is that SPEEK membranes exhibit low chemical stability and poor mechanical properties when applied to vanadium redox flow batteries, severely hindering their application. This invention addresses this issue by attaching hydrophilic sulfonic acid groups to the benzene ring and N and O six-membered oxazine rings. This retains the characteristics of benzoxazine materials, such as low curing shrinkage, high modulus, high strength, good heat resistance, and low water absorption, while enhancing proton conductivity. By blending SPEEK with high proton conductivity and then thermally curing it to achieve thermal crosslinking, a covalently crosslinked membrane with a network structure is prepared.

[0005] A blended thermally crosslinked separator for vanadium redox flow batteries, the main body of which is sulfonated polyether ether ketone (SPEEK), which also contains a crosslink of sulfonated benzoxazine and sulfonated polyether ether ketone.

[0006] The degree of sulfonation of sulfonated polyether ether ketone is 60-70%.

[0007] The thickness of the cross-linked film after thermosetting is 5-50 μm, preferably 10-30 μm.

[0008] The above-mentioned method for preparing the co-blended thermally crosslinked separator for vanadium redox flow batteries includes the following steps: Step 1: Preparation of sulfonated benzoxazine; Step 2: Sulfonated benzoxazine and sulfonated polyether ether ketone are added to an organic solvent as a casting solution. After coating and molding, the mixture is heated for thermal crosslinking to obtain a blended thermal crosslinked membrane.

[0009] In step 2, the weight percentage of sulfonated benzoxazine in the total weight of sulfonated benzoxazine and sulfonated polyether ether ketone is 1-40%, preferably 5-25%.

[0010] In step 1, the preparation method of sulfonated benzoxazine includes the following steps: 4,4'-Diaminodiphenylmethane and paraformaldehyde were dissolved in a solvent, and hydroxybenzenesulfonate was added to carry out a polymerization reaction. Ethanol was added to precipitate the product, and the product was protonated by acid solution to obtain sulfonated benzoxazine.

[0011] The molar ratio between 4,4'-diaminodiphenylmethane, paraformaldehyde, and hydroxybenzenesulfonate is 1:3-5:1-3.

[0012] The polymerization reaction conditions are 70-100℃ for 1-10 hours.

[0013] In the protonation treatment of the acid solution, concentrated hydrochloric acid is used, and the weight ratio of the product to concentrated hydrochloric acid is 3:0.5-2.

[0014] In step 2, the thermal crosslinking conditions are 80-200℃ for 1-24 hours.

[0015] The above-mentioned thermal cross-linked membrane is used in flow batteries.

[0016] The aforementioned flow battery is an acidic vanadium redox flow battery in which both the positive and negative electrodes are graphite carbon plates and both the positive and negative electrode electrolytes are tetravalent vanadium solutions. Beneficial effects

[0017] This invention involves thermally crosslinking benzoxazine with sulfonated polyether ether ketone (PEE ketone) to form a membrane. The resulting thermally crosslinked membrane exhibits properties including optimized ion selectivity and improved mechanical properties, thus developing a new generation of high-performance PEMs for VRFB systems. By incorporating hydrophilic benzoxazine into PEE ketone and then thermally crosslinking the resulting membrane using a thermosetting ring-opening network crosslinking structure, the invention effectively enhances the vanadium barrier capacity of the membrane, thereby significantly improving its ion selectivity and increasing the coulombic efficiency (CE) of the vanadium redox flow battery. Furthermore, it also improves the membrane's mechanical properties and dimensional stability. Attached Figure Description

[0018] Figure 1 It is a) the NMR spectrum of benzoxazine and b) the infrared image. Figure 2Images a) and b) are electron microscope (EM) images of films formed by a one-step heating method, and images c) and d) are EEM images of films formed by a temperature-programmed method. Both blend films are SPEEK-SBA-20%. Figure 3 The values ​​are a) proton conductivity, b) water absorption swelling rate, c) tensile strength and d) ion permeability of SPEEK / SBA-X (X=0%, 5%, 10%, 15%, 20%, 25%). Figure 4 This is a schematic diagram of a flow battery: a) Performance diagram of a vanadium redox flow battery, b) CE, c) VE, d) EE at 40-240 mA cm⁻¹. -2 At current density.

[0019] Figure 5 Figure a) shows the cycle test results of a full vanadium redox flow battery. Detailed Implementation

[0020] This invention discloses a sulfonated benzoxazine with sulfonic acid groups, which is added to a sulfonated polyether ether ketone substrate in a certain proportion (5-25%) and then prepared into a thermal crosslinked film by thermosetting method.

[0021] The sulfonated benzoxazine material in this invention, after being heated by a programmed temperature, opens the six-membered ring of the oxazine to form a cross-linked network structure, forming sulfonated polybenzoxazine, which greatly improves ion selectivity and the mechanical strength of the membrane, and the remaining sulfonic acid groups form hydrophilic channels, enhancing proton conductivity.

[0022] For the materials in this invention, the degree of sulfonation of sulfonated polyether ether ketone is controlled at 60-70%, and an excessively high degree of sulfonation may affect film formation.

[0023] Example 1 Preparation of sulfonated benzoxazine materials Synthesis of sulfonated benzoxazine material: 50 ml of dimethyl sulfoxide was added to a 250 ml three-necked flask, followed by 2.50 g (12.5 mmol) of 4,4'-diaminodiphenylmethane and 1.50 g (50 mmol) of paraformaldehyde. The mixture was stirred at room temperature for 2 h, and then 4.90 g (25 mmol) of sodium 4-hydroxybenzenesulfonate was added to the reaction system. The reaction was carried out at 90 °C for 4 h, and then cooled. The mixture was precipitated with a large amount of anhydrous ethanol, filtered, and dried to obtain 6.2 g of white powder solid, which was sodium sulfonate type benzoxazine monomer. Then, 3 g of sodium sulfonate type benzoxazine material was added to a 100 ml three-necked flask, and 1 ml of concentrated hydrochloric acid was added for protonation to obtain sulfonated benzoxazine material.

[0024] Example 2: Preparation of SPEEK / SBA blend membrane SPEEK was prepared by adding PEEEK powder to a 1000 ml three-necked flask and then sulfonating with 98 wt.% sulfuric acid for 5 h. A SPEEK / SBA blend membrane was then prepared using the following method.

[0025] SPEEK and SBA were dissolved in dimethyl sulfoxide at a concentration ratio of 1.5 g / 10 ml, and specific volumes of each solution were weighed and mixed according to their mass fractions. The mixed casting solution was ultrasonicated, mixed, and allowed to stand to form a homogeneous SPEEK / SBA casting solution. This solution was then coated onto a glass plate using a 250 μm doctor blade and dried using a programmed temperature method: 80℃ for 3 h, 140℃ for 4 h, 160℃ for 2 h, 180℃ for 2 h, and 200℃ for 2 h. This programmed temperature method was used to slow down the solvent evaporation rate as much as possible, ensuring that the benzoxazine monomers underwent a thermal crosslinking reaction in the presence of the solvent. The prepared blend film is denoted as SPEEK / SBA-X, where X represents the mass percentage of SBA in the total material.

[0026] If benzoxazine is not subjected to the sulfonation treatment as in Example 1, it cannot be dissolved in DMSO and cannot be blended with SPEEK.

[0027] Test methods swelling rate and water absorption rate The membrane's SR (swelling ratio) and WU (water absorption ratio) are obtained from the following two equations:

[0028] In the formula, d and W represent the diameter and mass of the membrane in the wet and dry states, respectively.

[0029] Mechanical properties At a tensile speed of 5 mm / min -1 The mechanical properties of the membrane were obtained using a universal testing machine. Samples were cut into strips of 35 mm × 10 mm, and the wet membrane surface was wiped dry before testing. To reduce testing error, three samples were tested for each membrane, and the data were averaged. The formula for calculating the tensile strength of the thin film sample is as follows:

[0030] In the formula, F Max The maximum tension is represented by W and D, which are the width and thickness of the sample mold, respectively.

[0031] Proton transfer rate The proton transfer rate of the membrane was measured using electrochemical impedance spectroscopy on an electrochemical workstation (Solartron analytical 1470E+1260A). The sample was clamped between two circular titanium plates, which were secured with button battery clips. The measurement frequency was 10 Hz. 3 Up to 10 6 Between Hertz, the AC amplitude is 5 mV. The proton transfer rate of the membrane was measured using the latest method from Professor Li's team, and the calculation formula is as follows:

[0032] In the formula, σ is the proton transfer rate of the membrane. L is the thickness of the sample. R is the impedance of the membrane. A is the effective area of ​​the membrane, i.e., the area of ​​the titanium sheet.

[0033] The film surface resistance can be calculated using the following formula:

[0034] R A It is the film surface resistance.

[0035] Vanadium ion permeation rate and ion selectivity With an effective area of ​​1.77 cm 2 The test was conducted in an H-type diffusion cell. One diffusion cell contained 50 mL of 1.5 M VOSO4 / 3.0 M H2SO4 solution, and the other diffusion cell contained the same volume of 1.5 M MgSO4 / 3.0 M H2SO4 solution to balance ionic strength and osmotic pressure. Magnetic stirring was used during the test to reduce concentration polarization. Samples were taken from the MgSO4 / H2SO4 solution every 24 h, and the absorbance was measured at 762 nm using a UV-Vis spectrophotometer. The concentration of VOSO4 / H2SO4 was determined using a standard absorbance / concentration curve. 2+ The concentration of vanadium. The vanadium permeation rate can be calculated using the following formula:

[0036] Where V B The volume of the MgSO4 / H2SO4 solution is 50 ml in this experiment; C B (t) represents the VO in the MgSO4 / H2SO4 solution at time t. 2+ Ion concentration; C A VO in VOSO4 / H2SO4 solution 2+ The concentration can be considered a constant if the experimental time is not too long, to simplify the calculation; A and L are the effective membrane area and membrane thickness, respectively; P is the vanadium ion permeation rate.

[0037] Ion selectivity is defined as the ratio of proton transfer rate to VO 2+ The ratio of permeation rates is calculated using the following formula:

[0038] Basic characterization of membranes Figure 2 The images show surface and cross-sectional electron micrographs of the blended film under different heating conditions (one-step heating method, i.e., 180℃ for 12h and programmed temperature rise method), indicating that direct high-temperature heating will lead to film defects; and from images c and d, it can be concluded that SBA and SPEEK have good compatibility and SBA can be uniformly dispersed. Figure 4 Tensile strength tests showed that the cross-linked network structure can improve the mechanical strength of the diaphragm, and the reduction in both water absorption and swelling rate indicates that the SBA material inhibits the movement of the flexible chain.

[0039] Single battery performance The performance of VRFB was tested using a homemade flow battery system, which consisted of a membrane (effective distance 10.5cm). 2 It consists of two carbon felt electrodes, two graphite plate current collectors, and a pair of housings. The membrane-separated negative electrode electrolyte (10 ml 1.5 M V) 2+ / V 3+ 3M H2SO4) and positive electrode electrolyte (10ml 1.5M VO) 2+ / VO2 + 3M H2SO4), and is sandwiched between two electrodes. For charge-discharge testing, the cutoff voltages for charging and discharging are 1.7V and 0.8V, respectively, and the test current densities are 40, 60, 80, 100, and 120 mA cm⁻¹. -2 For cyclic testing, a constant current density of 120 mA cm⁻¹ was used. -2 Tested at the same cutoff voltage. Nitrogen protection was used during the test. The coulombic efficiency (CE), voltage efficiency (VE), and energy efficiency (EE) of the battery were calculated using the following formulas:

[0040] in C d and C c These are discharge capacity and charging capacity, respectively. E d and E c These are discharge energy and charging energy, respectively.

[0041] The VRFB performance of the SPEEK / SBA-X blend membrane was evaluated (at 40–240 mA cm⁻¹). -2 (Under a series of current densities). For example... Figure 4As shown, thermal crosslinking with SBA can significantly improve the battery performance (CE) of SPEEK films. This result indicates that the network structure formed by thermal crosslinking SPEEK and SBA can effectively alleviate vanadium ion permeation and effectively improve battery performance. Furthermore, it can be seen that the preferred range for the amount of SBA added is 5-20%, and increasing it to above 25% leads to a decrease in battery efficiency.

[0042] Vanadium ion permeability test like Figure 3 The vanadium ion permeation of the membrane decreases with increasing doping concentration (d). This indicates that the thermally cross-linked network structure can inhibit the expansion of SPEEK water channels, thereby slowing down the transport of bulk ions.

Claims

1. A blended thermal cross-linked diaphragm for all-vanadium redox flow battery, characterized in that: The main component is sulfonated polyetheretherketone (SPEEK), which also contains cross-linked products of sulfonated benzoxazine and sulfonated polyetheretherketone.

2. The blended thermal cross-linked diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: The sulfonation degree of sulfonated polyetheretherketone is 60-70%.

3. The blended thermal cross-linked diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: The thickness of the cross-linked film after thermal curing is 5-50 μm, preferably 10-30 μm.

4. The method for preparing the blended thermal cross-linked diaphragm for all-vanadium redox flow battery according to claim 1, characterized in that: The steps include: Step 1: Preparation of sulfonated benzoxazine; Step 2: Add sulfonated benzoxazine and sulfonated polyetheretherketone into an organic solvent as a casting liquid, and after coating and forming, heat-crosslink at elevated temperature to obtain a blended heat-crosslinked diaphragm.

5. The method for preparing the blended thermal cross-linked diaphragm for all-vanadium redox flow battery according to claim 4, characterized in that: In step 1, the preparation method of sulfonated benzoxazine comprises the following steps: dissolving 4,4'-diaminodiphenylmethane and polyformaldehyde in a solvent, adding hydroxybenzenesulfonate for polymerization, adding ethanol for precipitation, and subjecting the product to protonation treatment with an acid solution to obtain sulfonated benzoxazine.

6. The method for preparing the blended thermal cross-linked diaphragm for all-vanadium redox flow battery according to claim 5, characterized in that: The molar ratio of 4,4'-diaminodiphenylmethane, paraformaldehyde and hydroxybenzenesulfonate is 1:3-5:1-3.

7. The method for preparing the blended thermal cross-linked diaphragm for all-vanadium redox flow battery according to claim 5, characterized in that: The polymerization reaction conditions are 70-100°C for 1-10h.

8. The method for preparing the blended thermal cross-linked diaphragm for all-vanadium redox flow battery according to claim 4, characterized in that: In the protonation treatment with an acid solution, concentrated hydrochloric acid is used, and the weight ratio of the product to the concentrated hydrochloric acid is 3:0.5-2.

9. The method for preparing the blended thermal cross-linked diaphragm for all-vanadium redox flow battery according to claim 4, characterized in that: In the step 2, the heat crosslinking condition is 80-200° C. for 1-24 h.

10. Use of the thermal cross-linked membrane according to claim 1 in a liquid flow battery.